Classical Universities in the Scientific and Technological Development of the Russian Empire and the USSR: Leaving the Ivory Tower - M. V. Gribovskiy (Moscow Polytechnic University, 2024)
The purpose of the article is to characterize the dynamics of changes in the role of classical universities in the scientific and technological development of the Russian Empire and the USSR, from the point of view of their involvement in the development of the real sector of the economy. The relevance of the study is related to the ongoing discussions about the higher education optimal model.The novelty is determined by the focus of the study, the breadth of the subject in geographical and chronological terms, and the materials used for analysis.The conducted research made it possible to clarify ideas about the elitist and anti-utilitarian nature of classical universities stemming in part from the principles of the Humboldtian model, the reception of which was carried out in Russia since the 19th century. The components of the activities of the imperial university were established, which ensured its connection with industry and the practical sphere. These components include: the work of some departments (primarily the department of technology), the promotion of ideas of industrial development in Russia by the professors, participation in all-Russian manufacturing (art and industrial) exhibitions, and the implementation of research work by universities commissioned by industrial enterprises; It is shown how during the First World War the emphasis on the practical component of higher education activities increased, for which it itself was not quite ready.Particular attention is paid to the profound (and not entirely positive) transformation that universities underwent in the first Soviet decades. In the context of decreasing attention to research activities and the "disaggregation" of universities in the early 1930s their potential has weakened noticeably. However, the correction of the scientific and educational policy of the times of the mature Soviet Union and the development of economic contractual issues have already occurred since the 1950s-1960s lead to an increased influence of universities on the development of the real sector of the domestic economy while reducing the share of fundamental research.